Верить больше некому - Тамоников Александр Александрович (Спецназ, 2013)
Экземпляры: Абонемент (20220113) / Инвентарный номер: 48768 / Цена: 85.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6